THE BASICS OF A NATIONAL HEALTH INFORMATION SYSTEM IN DENTISTRY - Claudia-Gabriela Mateiaş; Alexandru-Titus Farcaşiu; Mihaela Păuna (Amaltea Medical Publishing House, 2018)
National Health Information Systems are a widely accepted concept as a step forward for improving health services. In their simplest form, Health Information Systems are represented through Electronic Health Records (EHR) and offer a standardized storage and retrieval environment for patient information including personal data, case history, diagnostics and treatments. Such a system needs to be easy to access and use, sure, stable and standardized. Accessibility can be enhanced by using the internet to provide connectivity from anywhere and from any environment to the central database; ease of use is created by the intuitive and simplified interface. Security and stability are provided by the implementation of internationally accepted security protocols and the choice of a non-vulnerable database and operating system. Standardization is created by introducing international systems design standards, as well as diagnostic and treatment codes. Used nationally (and in the nearby future, internationally), the systems may contribute to research and development of new treatments and standardizing current practices.